Statistical tools to evaluate sensory data fro testing fruit quality of Musa - Korie, S.; Walker, P.; Ortíz, R.; Vuylsteke, D.R.; Ferris, R.S.B. (International Society for Horticultural Science, 2000)
Recent successes in the conventional cross-breeding of plantains and cooking bananas by genetic improvement programmes will inevitably lead to an increase in the number of new clones that require testing before release to farmers. In most cases testing focused on disease resistance and yield but little attention was given to fruit quality. The International Institute of Tropical Agriculture (IITA) has developed a procedure for testing the fruit quality of landraces and hybrid Musa genotypes. This fruit quality procedure measures a wide range of characteristics using both objective physical tests and subjective sensory evaluation. The most diverse and difficult datasets to interpret are recorded from sensory analyses. Therefore, a computer programme for data management and statistical analysis was compiled at IITA. This computer programme enables researchers to access their datasets to make selections based on statistically verified results of fruit quality. This paper describes the programmes developed in Genstatâ 5-Release 2.2 to analyse the sensory datasets.